Socialna diverziteta v luči inkluzivnosti istospolno usmerjenih pripadnic in pripadnikov v slovenski vojski - Vuk, Pavel (Teorija in praksa, 2022)
The article brings to Slovenia the first military sociological research on the inclusion of homosexual members in the Slovenian Armed Forces (SAF). Based on focused structured interviews, we studied the issue from two standpoints: the social (perception of lesbians and gays) and institutional aspect (perception of the SAF). The research showed that in a largely heteronormative environment, homosexual members of the SAF are exposed to various forms of verbal discrimination, despite the formal protection of their dignity and integrity. The need to discuss this quite taboo issue is obvious, as is the need to acknowledge the benefits of social diversity in modern military organisations
Keywords: discrimination; diskriminacija; gays; geji; Homoseksualci; Homoseksualci in lezbijke v vojski; homoseksualnost; homosexuality; istospolno usmerjene osebe; lesbians; lezbijke; Slovenian Armed Forces; Slovenksa vojska